Urban governance and smart city planning : lessons from Singapore - Allam, Zaheer (Emerald points., 2020)
In a world characterised by rapid urbanisation it is increasingly difficult to devise urban governance models which are resilient, safe and inclusive, and that also preserve the environment. This book takes Singapore, a leader in this field, as a case study, looking at its successes in urban governance and smart city planning. Through the lens of environmental sustainability, the author examines Singapore's recent adoption of technological tools, which have led to increased efficiency and performance, and have also supported its economic ambitions. The book unveils a unique and critical insight into Singapore's approach. Considering the historical, political and technological context, the author shares the techniques and key projects that have contributed to the all-important improvement of liveability levels in the city state.